Escala metacognitiva para idosos: elaboração de itens e análise dos parâmetros psicométricos - França, Alex Bacadini (Universidade Federal de São Carlos, 2013)
New studies and ways of intervening with the elderly population are emerging, given that we now know that aging not necessarily accompanied by cognitive decline. Along with studies on other aspects of aging, the metacognitive processes that coordinate cognitive performance, have begun to acquire importance in the literature over the past four decades. Metacognition represents thoughts and knowledge that individuals have about their own thoughts and cognitive processes. Two of its basic elements are: metacognitive knowledge, characterized by awareness of the processes and skills necessary to perform a given task, and control or cognitive self-regulation, which includes judgment about the effectiveness of the strategies being used and the establishment of new ones. Considering that metacognition facilitates the effective performance of activities and given the lack of Brazilian instruments to measure it, the main objective of the study is the development of a scale for the assessment of metacognition among the elderly and analysis of the validity and accuracy of this scale. The first stage of the study involved the development of the Metacognition Scale - Senior (EMETA-S), for each topic, the participant, must choose from four possible answers, the one that best characterizes him or her. The second stage aimed to investigate evidence of content validity. For this step, the instructions and the 74 original items of the instrument were sent to three experts. The index of agreement resulting from the analysis of the responses of the experts was 68%. The scale was also tested with a sample of 15 participants (60 aged years or over) in verify whether or not the instructions and the items were understandable, which resulted in some changes in the wording of the instructions and items, as well as in the descriptors of the scale, constituting the third stage of the study. A factor analysis performed on the data gathered with a sample of 194 participants revealed the presence of two factors: selfregulation and metacognitive knowledge, accounting for 27.18% of the variance in the responses. After exclusion of items that had factor loadings below 0.30, items misunderstood by participants and items that were highly similar to others items, the final version of the EMETA-S was composed of 27 items, with internal consistency of 0.85. No significant differences were found between the average performance with respect to variables such as gender, education and age of participants. The analysis of the validity and accuracy of the items indicated suitability of the concept initially proposed and good internal consistency of the scale.
Metacognitive scale for the elderly: development of items and analysis of psychometric parameters
Keywords: Psicologia cognitiva; Metacognição; Instrumentos de medida; Envelhecimento; Medidas psicológicas; Metacognition; Psychological measures; Aging; CIENCIAS HUMANAS::PSICOLOGIA